The Penguin dictionary of psychology - Reber, Arthur S., 1940-; Reber, Emily S. (London : Penguin, 2001)
Completely revised and updated, this new edition explores the latest developments in psychology, psychiatry and related fields, including new material on neuroscience and social psychology.
Previous ed.: 1995.
Keywords: Psychology -- Dictionaries; Psychology